1992
DOI: 10.1007/bf00270037
|View full text |Cite
|
Sign up to set email alerts
|

Nile red staining of lysosomal phospholipid inclusions

Abstract: We have employed the fluorescent dye nile red to distinguish between normal cells and cells containing lysosomal accumulations of phospholipids. When fibroblasts from an individual with a genetic deficiency in lysosomal sphingomyelinase activity (Niemann-Pick disease) were stained with nile red and visualized by fluorescence microscopy, orange-colored inclusions were observed throughout the cytoplasm. The orange fluorescent bodies could be distinguished from the neutral lipid droplets that fluoresce a brillian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 15 publications
2
57
1
Order By: Relevance
“…Microscopy is another method used for studying uptake and distribution of NPs (18,22,37,43). However, microscopy should be employed with care in the assessment of dye leakage, as free hydrophobic dyes will bind to intracellular hydrophobic molecules resulting in both diffuse and spotted staining pattern (12,24,30,33), thereby making the dye hard to separate from the fluorescence of intact NPs. In a previous study, we have shown that PBCA-NPs with NR668 are taken up in PC3 cells by endocytosis, verified by the use of time consuming intracellular spectral microscopy and fluorescence-lifetime imaging microscopy (FLIM) (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopy is another method used for studying uptake and distribution of NPs (18,22,37,43). However, microscopy should be employed with care in the assessment of dye leakage, as free hydrophobic dyes will bind to intracellular hydrophobic molecules resulting in both diffuse and spotted staining pattern (12,24,30,33), thereby making the dye hard to separate from the fluorescence of intact NPs. In a previous study, we have shown that PBCA-NPs with NR668 are taken up in PC3 cells by endocytosis, verified by the use of time consuming intracellular spectral microscopy and fluorescence-lifetime imaging microscopy (FLIM) (12).…”
Section: Discussionmentioning
confidence: 99%
“…Various procedures have been developed to evaluate NP-labeling stability (18,20,23,(25)(26)(27)(28)(29). However, the majority of these assays do not include cells or serum, which could strongly affect dye release as these serve as acceptor compartments for released dye in vivo (18,24,(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…These images were analyzed by the Factor Analysis of Medical Image Sequences (FAMIS) algorithm, which provides factor curves and images (31,32). The ability to colocalize 7KC (emitting a blue fluorescence under ultraviolet [UV] light) (33) and cellular lipids stained with NR is possible because of the overlap of the emission spectra of 7KC with the excitation spectra of NR (33)(34)(35). In addition, subcellular fractionation associated with gas chromatography and mass spectrometry was used to characterize NR-positive cytoplasmic structures.…”
mentioning
confidence: 99%
“…Fluorescence and light microscopy have been instrumental in locating and identifying lipid components of atherosclerotic lesions in animal models and human biopsy tissues (Brown et al 1992;Seifert 1989;Lupu et al 1987;Fowler and Greenspan 1985;Kruth 1984aKruth ,b,1985Kruth and Fry 1984). Immunohistochemical (IH) methods have been used to distinguish populations of smooth muscle cells and macrophages in atherosclerotic lesions (Masuda and Ross 1990;Rosenfeld et al 1987;Tsukada et al 1986), and many authors have used electron microscopy to characterize cell types and investigate intracellular aspects of atherosclerosis (Masuda and Ross 1990;Lupu et al 1987;Rosenfeld et al 1987).…”
mentioning
confidence: 99%